Perceptions of the sports community toward gymnastics achievement in Semarang City - Unique Mierdha Denata Winarko; Said Junaidi (CV Rezki Media, 2025)
Background: Gymnastics is a fundamental sport that supports physical fitness development and long-term athletic performance through complex physical demands such as strength, flexibility, balance, coordination, and explosive power. However, its development as an achievement sport often receives limited structural and institutional support at the local level. Objectives: : This study aimed to analyze the perceptions of the sports community toward gymnastics achievements in Semarang City and to identify discrepancies between conceptual support and perceived developmental conditions. Methods: A quantitative descriptive survey design was employed involving 60 respondents from the sports community, including sport science students, physical education teachers, and sports practitioners. Data were collected using a validated and reliable closed-ended questionnaire measuring three perception indicators: acceptance, understanding, and appraisal of gymnastics as an achievement sport. Responses were assessed using a four-point Likert scale. Data analysis was conducted using descriptive statistics alongside validity and reliability testing. Results: Item-level analysis indicated positive perceptions, with mean scores ranging from 3.05 to 3.79, reflecting strong recognition of gymnastics’ value and potential. However, classification of total perception scores showed that 58.33% of respondents rated the current condition of gymnastics development as very poor. This contrast highlights a clear gap between conceptual appreciation and perceived realities, particularly regarding infrastructure availability, coaching quality, and competition opportunities. Conclusions: The sports community in Semarang City demonstrates strong conceptual support for gymnastics as an achievement sport, yet perceives substantial limitations in its practical development. Strengthening facilities, coaching systems, and competitive structures is essential to transform positive perceptions into sustainable athletic performance.